Maximal oxygen levels as an incremental exercise to optimise individual training prescription with the aim of rectifying weaknesses of elite Algerian soccer - Mime, M.; Zerf, M.; Hadjar Kherfane, M.; Beboucha, W. (International Journal of Human Movement and Sports Sciences, 2019)
Purpose: This study aims to provide the Algerian soccer trainers with a systematic method to control and interpret the Algerian soccer's progress. Recommend by soccer studies based on new high-tech to monitor intensity aimed at a competitive superiority of soccer players. Performed based on direct relationship VO2max, intensity and distance covered in elites match. Methods: to esteem the weaknesses of elite Algerian soccer. This controlled study focused on a yo-yo (IR1) test as a reliable, valid predictor of high-intensity aerobic capacity and VO2max athletes levels, which is able to discriminate the differences between player's post-games and player's ability levels. Investigated in this study as a protocol to classify 59 male soccer players under 18 years, labelled on their VO2max levels and their relationships with body fat index studies. Results: All statistical procedure results advance the players with high VO2max levels up than 59 ml/kg/min, allows this category of players to record a difference of 8.98% VO2max levels, 1160.86 m of distance covered, -1,27% of BFP and -4,55 ml/ kg/min of BMI higher compared to the other fewer categories records. Conclusions: Our results approve the Yo-Yo intermittent recovery level 1 (Yo-Yo IR1) test as a valid and reliable test to monitor improvements or decrements of soccer physiological and anthropometrical training concept game demands. It can be concluded in this study as simple and valid data to predict the excess of body fat index on the request aerobic fitness claims for demanding soccer top player profile.